Microfinance: Where are we today and where should the research go in the future?. (November 2017) - Chen, Juanyi; Chang, Amber Y; Bruton, Garry D
Over the past two decades, there have been substantial efforts to expand the impact of microfinance around the world, especially in emerging economies. This commentary and Special Issue of International Small Business Journal, seeks to better the understanding of both the contributions and limitations of microfinance in terms of fostering entrepreneurship and economic development. Specifically, we review prior research to understand whether and how microfinance can help to encourage entrepreneurial activity as well as to reduce poverty. We then highlight the gaps in the existing literature and lay out an agenda for future research in this domain.